2008
DOI: 10.1097/mcc.0b013e32830a4c5d
|View full text |Cite
|
Sign up to set email alerts
|

Update on cardiac arrhythmias in the ICU

Abstract: Supraventricular arrhythmias, especially atrial fibrillation, occur frequently in ICU patients. Intensivists not only treat atrial fibrillation itself but also its complications and the complications of the therapies used to prevent these complications. In ICU patients, ventricular arrhythmias have ominous implications because they usually portend either a major cardiac or a systemic dysfunction or both.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 51 publications
1
28
0
1
Order By: Relevance
“…Reemphasized by the present study, even though arrhythmias may be an early sign of sepsis (1) and are associated with adverse outcomes, there is lack of data regarding evidence based treatment strategies. Moreover, present data mainly focuses on treatment and prevention of A fib (3).…”
Section: Discussionmentioning
confidence: 99%
“…Reemphasized by the present study, even though arrhythmias may be an early sign of sepsis (1) and are associated with adverse outcomes, there is lack of data regarding evidence based treatment strategies. Moreover, present data mainly focuses on treatment and prevention of A fib (3).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of various cardiac arrhythmias in septic patients has been demonstrated by several clinical reports and studies [21][22][23][24][25]. These arrhythmias may be explained by autonomic dysfunction or impairment and involvement of the cardiac conduction system rather than to pre-existing cardiac co-morbidities [26,27].…”
Section: Introductionmentioning
confidence: 98%
“…Since then, differ-ent types of supra-ventricular, ventricular arrhythmic tachycardia and arrhythmic bradycardia in septic critically ill patients have been described [21,[29][30][31][32] (Table 1). Several large epidemiological [24,25,[33][34][35] and small cohort studies [36][37][38][39] have shown strong evidence of new onset arrhythmic tachycardia immediately before the onset of postoperative sepsis.…”
Section: Prevalence and Risk Factorsmentioning
confidence: 99%
“…Other clinical aspects of sepsis-induced cardiac dysfunction are tachyarrhythmias [44,45], right heart failure [46,47], elevated troponin [48,49] and B-type natriuretic peptide levels [50][51][52].…”
Section: The Heart In Sepsismentioning
confidence: 99%